HOW CSR DRIVES COMPETITIVE PERFORMANCE: A MEDIATION-MODERATION ANALYSIS OF CUSTOMER SATISFACTION AND INFORMATION QUALITY (Contemporary Journal of Social Science Review, 2025)
The objective of this study is to evaluate the determination of corporate social responsibility (CSR) on firm competitive performance (FCP) via the mediating role of customer satisfaction (CST) and moderating role of CSR information quality (CIQ). The role of CSR information quality on strengthening CSR-CST relationship is also studied in this research. Furthermore, it has followed a structured questionnaire to collect data of 237 FMCG companies of top-level, middle level and lower management. A two-stage SEM technique was used for the data analysis. Measurement Model, to evaluate the reliability and validity of the instrument; and Structural Model, to evaluate the strength of the relationships between the underpinning variables. The main discovery of this study confirmed that CSR positively and significantly affects CST. Furthermore, the findings show that CST play an important mediating role between CSR and FCP. In addition, the results revealed that CSR information quality (CIQ) moderated the relationship between CSR and CST, enhancing the total effect. Through this study, therefore, the author makes a substantial contribution to the literature in general and the FMCG insecurity literature in Pakistan by providing a better understanding of how industries can harness CSR for the purposes of strategic financial and social goals and objectives, sustainable competitive advantage.